Changes in prescribing patterns and access to immune checkpoint inhibitors in german lung cancer patients – a claims data analysis - Julia Walter; Blerina Resuli; Laura Sellmer; Diego Kauffmann-Guerrero; Toki Bolt; Chukwuka Eze; Jürgen Behr; Amanda Tufman (BMC Public Health)
Abstract Background Recently, immune checkpoint inhibitors (ICIs) have driven profound changes in the treatment of non-small cell lung cancer (NSCLC). Their rapid integration into clinical routine is crucial for patient outcomes. However, prescribing patterns may not change immediately after authorization. Therefore, in this study we investigated factors associated with the adoption of ICI therapy for patients with advanced lung cancer in Germany following the initial regulatory approval. Methods In this study we used German health insurance claims of 36,727 lung cancer patients diagnosed in 2015–2016. We included pre-treated patients with advanced disease. Factors potentially influencing the adoption of ICI therapies were analyzed, including demographics, residence type, hospital size, comorbidities, and metastasis location. Changes in prescribing patterns for ICI therapies were evaluated over three years using population-at-risk calculations with statistical analysis conducted using techniques including multivariate Cox regression. Results Overall, we identified 9,726 pre-treated patients with advanced lung cancer in our dataset. Of these, 285 received ICI therapy during the course of the disease. These initial patients receiving ICI therapy were significantly younger and were more often treated in bigger hospitals. At first, uptake of ICI therapy was slow but started to increase from 1.1% in 01/2017 to 8.6% in 12/2019. Multivariate Cox regression showed that being treated in a bigger hospital (HR = 1.49, p = 0.001), having M1a vs. M1b or c metastases (HR = 2.65, p < 0.0001), being diagnosed in 2016 vs. 2015 (HR = 3.39, p < 0.0001), and having a comorbidity of COPD (HR = 1.46, p = 0.004), led to higher, faster adoption of ICI therapy. Conclusion Introducing novel therapies necessitates a deliberate focus on disseminating information and enhancing accessibility across healthcare facilities of varying sizes.